Clustering by Employee Personality, Modern Working World Perspectives on Work Efficiency in the Organizations - Krit Jarinto; Laddawan Ridsomboon (My University, 2023)
The purpose of this study is to classify the employees of a multinational company with Thai operations. A two-step cluster analysis technique is used in this quantitative study to analyze the data. Six variables are used to group individuals: gender, education level, type of international firm, personality, length of employment with the organization, and work efficiency. The research aims to help businesses build their human resource strategies, and several areas, including hiring, placement, and personal growth. This study distributed 446 questionnaire sets. Six clusters emerged from the two-step cluster analysis. Cluster 1 had the lowest work efficiency and the shortest work time, as characterized by Conscientiousness personality. Cluster 2, which was also characterized by Conscientiousness, had the highest work efficiency and moderate work duration of all groups. Cluster 3, which was distinguished by Emotional Stability, scored fourth in terms of job efficiency, and had a relatively long working time. Cluster 4 (Agreeableness) ranked fifth in work efficiency and had the longest work duration. Extraversion characterized Cluster 5, which ranked third in work efficiency and had a rather long work time. Finally, Cluster 6, which is defined by Openness to Experience, came in second in terms of work efficiency but had the lowest work length.
Keywords: Conscientiousness; Agreeableness; Openness to experience; Job Satisfaction and Organizational Behavior